STRATEGI PENGEMBANGAN USAHA PENGOLAHAN IKAN SALAI PATIN DI KABUPATEN KUANTAN SINGINGI - Gusfi Trianda; Geovani Meiwanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study discusses the Development Strategy for Salai Patin Processing Business in Kuantan Singingi Regency. This study aims to: (1) to analyze the strategy in developing salai patin processing business in Kuantan Singingi Regency, (2) to find out the factors that influence the strategy for developing salai patin processing business in Kuantan Singingi Regency. This type of research is qualitative research. There were 6 informants in this study, and one key informant. The results of this study are: (1) the strategy for developing a salai patin processing business in Kuantan Singingi Regency has fulfilled a good aspect, because it has carried out planning, implementation and supervision efforts in terms of coaching and assistance to farmers. And a SWOT analysis was carried out to identify each internal factor (strengths and weaknesses) and external factors (opportunities and obstacles) in the strategy for developing salai patin processing business in Kuantan Singingi Regency. (2) the factors that influence the development strategy for the salai patin processing business are the poor management of the fishery group and the processed salai patin processing products are still unable to compete in marketing. The research suggestions are: (1) the role of the government as a policy maker can monitor or supervise smoked fish processing groups so that they comply with the group's organizational principles. Conduct training for salai fish processing groups on how to manage groups that are good and right for the sustainability of the group and common goals; (2) processors of salai patin products located in Kuantan Singingi Regency should expand their market to develop their market share both inside and outside Riau Province. Keywords: Strategy, Salai Patin business